A Review of Acupuncture for the Treatment of Dry Eye Syndrome: Mechanisms, Efficacy, and Clinical Implications - Chen T; Feng LQ; Jin Y (International Journal of General Medicine)
Ting Chen,1 Lu-Qi Feng,2 Ying Jin2 1Medical School, Quzhou College of Technology, Quzhou, 324000, People’s Republic of China; 2Department of Acupuncture, Quzhou Traditional Chinese Medicine Hospital, Quzhou, 324002, People’s Republic of ChinaCorrespondence: Ying Jin, Department of Acupuncture, Quzhou Traditional Chinese Medicine Hospital, No. 117 of Quhua Road, Kecheng District, Quzhou, 324002, People’s Republic of China, Tel +86 15657026605, Email jinyingjy01@163.comAbstract: Dry eye disease (DED) is a prevalent ocular condition characterized by discomfort and vision impairment in affected individuals. This review discusses various etiologies of DED, including autoimmune, drug-induced, and mechanical factors, each with distinct underlying causes. Acupuncture, a traditional therapeutic modality, has garnered increasing attention in recent years as a potential complementary treatment for DED. Current clinical evidence demonstrates that acupuncture for DED, when performed by qualified practitioners following standardized protocols, exhibits favorable safety profiles with only mild and transient adverse reactions (eg, minor local bleeding, brief needling pain, or mild needle syncope) potentially occurring. This review provides a comprehensive analysis of recent studies investigating the underlying mechanisms, therapeutic efficacy, and clinical applications of acupuncture in the treatment of DED. Findings suggest that acupuncture enhances tear production, reduces ocular inflammation, and regulates nervous system function, offering a multifaceted approach to DED management. Clinically, acupuncture may reduce reliance on medications, thereby minimizing the risk of side effects and drug interactions. Additionally, it has the potential to improve patients’ quality of life by alleviating discomfort, enhancing ocular health, and promoting overall well-being. These insights underscore the role of acupuncture as a complementary treatment and highlight its implications for improving patient outcomes and guiding future research in this field.Keywords: acupuncture, dry eye disease, efficacy assessment, traditional Chinese medicine, treatment